Physical and Mechanical Properties of Particle Board Produced by Sawdust and Straw Rice - Zulkifli, Muhammad Ezzat; Zulkefli, Zulfadhli; azeli, Muhammad Afif Danish; Aslila Abd Kadir (Multidisciplinary Applied Research and Innovation, 2024)
Particle board is a widely used engineered wood product that offers numerous advantages, including cost-effectiveness, versatility, and sustainability. In recent years, there has been a growing interest in exploring alternative raw materials for particle board production to reduce dependence on traditional timber resources. This study investigates the physical and mechanical properties of particle boards manufactured using sawdust and straw rice as the primary raw materials, with resin and hardener serving as the binder. Physical properties (water absorption (WA)) and properties (bending test and tensile test) were determined based on the mixing ratios according to the standard. WA was measured after 7 hours and 24 hours of immersion in water.